Assessing delirium knowledge among health care professionals: findings from a scoping review - Chiara Muzzana; Irene Mansutti; Alvisa Palese; Dietmar Ausserhofer (BMC Nursing)
Abstract Background Delirium is highly prevalent among older adults in various healthcare settings. Healthcare professionals’ knowledge is crucial for preventing, recognizing, and managing delirium and delirium-related adverse outcomes. Despite its importance, little is known about how delirium knowledge is assessed. Objectives To map instruments and items used to assess delirium knowledge among healthcare professionals. Design A scoping review based on the methodological framework of Arksey and O’Malley (Int J Soc Res Methodol 8:19-32, 2005). Materials and methods A systematic literature search was performed in Medline, Embase, CINAHL, Scopus, and PsycINFO to include studies that assessed delirium knowledge among healthcare professionals. Results After removing duplicates, 760 studies were assessed for eligibility and 98 studies were included. Delirium knowledge was mainly assessed among nurses (57/98, 58.8%) and physicians (12/98, 12.4%) with a focus on critical care (32/98, 33.0%) over long-term care settings (4/98, 4.1%). Most studies used self-developed instruments (50/93, 53%), followed by original or modified versions of the Delirium Knowledge Questionnaire (14/93, 15%). Among the 32 identified instruments, limited evidence of validity and reliability was reported for six (18.8%). Analysis at the item level (n = 392 items) revealed five domains: (a) definition, signs and symptoms (81 items); (b) risk factors, incidence, and prevention (139 items); (c) detection and tools (89 items); (d) management and therapy (64 items); and (e) outcomes, prognosis and consequences (19 items). Conclusions Delirium poses a significant burden on patients and on the healthcare system. This scoping review provides a comprehensive overview on how healthcare professionals’ delirium knowledge has been assessed. Further research in this field is needed to provide stronger evidence of instruments’ validity and reliability and to explore delirium knowledge among healthcare professionals in long-term care settings.